Whitehorse waterfront and shipyard, Yukon River, ca. 1907 - Nowell, Frank H., 1864-1950 (1907)
Shows steamers WHITE HORSE, YUKONER, SELKIRK, COLUMBIAN, LA FRANCE, BAILEY, ZEALANDIAN, and others. Caption on image: Winter Quarters for Yukon River Boats To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number